ICT Integration in Secondary School Teaching And Learning: An Analysis of the Mauritian Context. - Veeraragoo, Vandana R. (2018)
The integration of Information and Communication Technology (ICT) into the teaching and learning process has become the major focus worldwide. It is clear that students now expect ICT to be part of their learning experience. The purpose of this study was to determine the level of ICT integration in the teaching and learning process among secondary educators in Mauritius and explore their attitudes towards ICT integration. The Diffusion of Innovation theory (Rogers, 1995) served as the main theoretical framework for this study. A quantitative research design was used in this study. The constructs are namely: usage of ICT in daily lives, perceived competence, ICT integration, attitudes, barriers and early or late adopters. The data were analyzed using both descriptive and inferential statistics for the quantitative data. To complement the findings and for triangulation purposes, semi structured interviews were conducted. A thematic approach was adopted to analyze the data. The findings confirmed those reported in the literature. A majority of educators have adequate knowledge of using ICT. Mauritian secondary educators’ attitudes towards ICT integration from highest to lowest in mean scores were: observability, relative advantage, complexity, and compatibility. They had moderate positive computer competence. However, low level of ICT supported teaching due to lack of infrastructure facilities and resources were found. The educators require training on ICT integrated pedagogical approaches. Educators indicated that the lack of time, their uncertainty, the unsuitable curriculum, the problematic access to equipment, the frequent technical problems and the lack of immediate technical support are some of the most significant factors affecting ICT use. Nevertheless, the study shows that there is a positive ground on which ICT can be successfully and meaningfully integrated in schools if educators have positive ICT attitudes and have quality ICT training. A profile of the Mauritian educators is presented and recommendations based on the research findings are discussed. The ongoing reform of the educational system provides a great opportunity to set up the right conditions that will facilitate the sound integration of ICT in secondary schools in Mauritius.